Prediction of late results of surgical treatment of traumatic retina detachment in eye injury of multiple origin - N. L. Leparskaya (Российский офтальмологический журнал, 2023)
Purpose. To evaluate the possibility of predicting the anatomical and functional results of surgical treatment of traumatic retinal detachment (RD) in trauma of various geneses, taking into account the clinical picture and the severity of the proliferative syndrome based on large clinical data.Materials and methods. A comprehensive analysis of the clinical picture (using 22 features) and long-term results of surgical treatment of 427 patients with traction traumatic RD (TRD) after open and closed eye injury was carried out. The patients were divided into 7 groups depending on the mechanism of injury. The observation period was 5 years.Results. The most severe proliferative syndrome was observed in TRD after an open injury: OEI A (contusions with scleral rupture), OEI D (double puncture wound) and OEI E (explosive trauma with scleral rupture), when both the process of mooring and PVR are present, as well as with CEI A (contusion) in the event that after the first operation PVR continued to progress. We found a direct dependence of PVR activity in TRD on the area of the detached retina and the presence of a traumatic cataract, and the inverse dependence on the presence of intraocular foreign body (IFB), its size and the ability of IFB to cause metallosis. A direct dependence of long-term functional results of treatment on the PVR stage, the area of detached retina and the diagnosed retinal rupture during the first vitreoretinal surgical intervention was established.Conclusion. In order to make the surgical treatment of TRD more effective, it is worth using antiproliferative drugs intravitreally during vitreoretinal surgery, especially in OEI A, OEI D and OGI E, when the proliferative syndrome is caused both by PVR and mooring, as well as in CEI A in the case of a pronounced PVR stage.